Study on the Copolymerization of Propylene with Norbornene Using Metallocene Catalysts - Rabagliati-Canessa, F (2012)
The copolymerization of propylene with norbornene, using the metallocene catalysts Me 2Si(2-Me-Ind) 2ZrCl 2 and Ph 2C(Flu)(Cp)ZrCl 2 was evaluated. The presence of norbornene decreases the polymerization activity in both systems. In the Me 2Si(2-Me-Ind) 2ZrCl 2 system, the decrease is ca. 80 % using 0.5 mL of norbornene while the addition of 2 mL reduces the activity by 97 %. The molecular weight of the materials decreases between 27,000 and 37,000 g/mol in the presence of norbornene. The Ph 2C(Flu)(Cp) ZrCl 2/MAO system has the same tendency, but the norbornene has a lesser effect on the activity, with 2 mL of comonomer reducing the activity ca. 80 %. The molecular weight decreased significantly with this system as well. The elongation at break of some of the materials was 80 times higher than the homopolymer and the Young s modulus slightly superior to the homopolymer. This indicates that it is possible to generate materials that keep the properties of a syndiotactic polypropylene but with good elastomeric properties. © Springer-Verlag 2012.